Echinoderms in the Bohemian Ordovician - Prokop,R.J.; Petr,V. (Journal of the Czech Geological Society, 1999)
An updated list of echinoderm and 'carpoid' groups and species in the Bohemian Ordovician is presented in the form of a table with a brief introduction.
Keywords: Echinodermata; Carpoidea; biostratigraphy; Ordovician; Bohemia